Survival probability and predictors for woman experience childhood death in Nigeria: “analysis of north–south differentials” (2012)
Background: Childhood mortality rate is high in Nigeria. There is dearth of information on the comparison of childhood mortality probability and its causal factors in the Northern and Southern Nigeria. This study was designed to fill these gaps. Methods: Nigeria Demographic and Health Survey, 2008 data was used. The first part of this study focused on women aged 15–49 who ever given birth to a child (n = 23,404), irrespective of the survival status of the child and the second part utilized all women aged 15–49 (N = 33,385). The outcome variable was experienced childhood mortality. Data was analyzed using Chi-square, logistic regression and Brass logit model. Results: Results showed that similar patterns of children’s death were observed in the two regions, but variation existed. Childhood mortality experienced was more pronounced in the North than the South, even when the potential confounding variables were used as control. Levels of education and wealth index showed an inverse relationship with childhood death in the regions (p < 0.05). The gap in childhood mortality experienced between the poorest and richest was wider in the North than the South. There was no significant difference in the risk of childhood mortality experienced by women in the urban and rural areas in the North (p > 0.05), but the difference was significant in the South (p < 0.05). The life-table mortality levels were lower in the North than the South, an indication of higher previous childhood mortality experience in the North than in the South. Across all childhood ages, the smoothed childhood mortality probabilities were consistently higher in the North than the South. Conclusion: Childhood mortality is higher in the Northern than Southern Nigeria. Improving women’s education, particularly in the North will alleviate childhood mortality in Nigeria.